A Measurement of the Angular Power Spectrum of the Cosmic Microwave Background with a Long Duration Balloon-borne Receiver - Crill, Brendan Patrick (California Institute of Technology, 2001)
This thesis describes BOOMERANG; a balloon-borne telescope and receiver designed to map the Cosmic Microwave Background (CMB) at a resolution of 10' from the Long Duration Balloon (LDB) platform. The millimeter-wave receiver employs new technology in bolometers, readout electronics, cold re-imaging optics, millimeter-wave filters, and cryogenics to obtain high sensitivity to CMB anisotropy. Sixteen detectors observe in 4 spectral bands centered at 90, 150, 240 and 400 GHz. The wide frequency coverage, the long flight duration, the optical design and the observing strategy all provide strong rejection of systematic effects. We report the in-flight performance of the instrument during a short test flight from Palestine, Texas, that mapped 230 square degrees and during a 10.5 day stratospheric balloon flight launched from McMurdo Station, Antarctica, that mapped ~ 2000 square degrees of the sky. The Antarctic data yielded a measurement of the angular power spectrum of the CMB between 50 < ℓ < 600 which shows a peak at ℓpeak = 197 ± 6 (1σ error). A maximum likelihood estimation of cosmological parameters within the cold dark matter (CDM) paradigm of structure formation indicates that the universe is flat with a precision of ~ 6% and that the density of baryons in the universe may be slightly higher than previously thought. The combination of observations of large scale structure (LSS) and the BOOMERANG power spectrum implies the presence of both dark matter and dark energy, or the existence of Einstein's cosmological constant.